2017
DOI: 10.1002/bmc.3947
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous densitometric determination of anthelmintic drug albendazole and its metabolite albendazole sulfoxide by HPTLC in human plasma and pharmaceutical formulations

Abstract: A new, simple, accurate and precise high-performance thin-layer chromatographic method has been developed and validated for simultaneous determination of an anthelmintic drug, albendazole, and its active metabolite albendazole, sulfoxide. Planar chromatographic separation was performed on aluminum-backed layer of silica gel 60G F using a mixture of toluene-acetonitrile-glacial acetic acid (7.0:2.9:0.1, v/v/v) as the mobile phase. For quantitation, the separated spots were scanned densitometrically at 225 nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“… 2 Due to the great clinical importance of ABZ, several analytical methods have been reported for its determination either in pharmaceutical dosage forms or in biological fluids. The reported analytical methods include: spectrophotometry, 3–9 spectrofluorimetry, 10–13 high-performance liquid chromatography (HPLC) 14–17 HPTLC, 18 thermogravimetry 19 and electrochemical methods. 20,21 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Due to the great clinical importance of ABZ, several analytical methods have been reported for its determination either in pharmaceutical dosage forms or in biological fluids. The reported analytical methods include: spectrophotometry, 3–9 spectrofluorimetry, 10–13 high-performance liquid chromatography (HPLC) 14–17 HPTLC, 18 thermogravimetry 19 and electrochemical methods. 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Albendazole is only detectable for a short time in plasma due to its rapid conversion to its major active metabolites such as ABZ-sulfoxide (ABZ-OX) and ABZ-sulfone (ABZ-ON) and subsequently low drug concentrations [ 6 ]. Various bioanalytical methods are available for analysis of ABZ and its metabolites in different biological matrices [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Wojnicz et al reported a LC–MS/MS method for the quantitation of ABZ and ABZ-OX in 200 μL plasma with a LLOQ of 5 and 10 ng/mL)[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rathod et al developed a LC–MS/MS method for the quantitation of ABZ and ABZ-OX in 100 μL plasma with a LLOQ of 0.3and 3 ng/mL respectively [ 13 ]. Pandya et al has a developed a HPTLC method for ABZ and ABZ-OX, has a LLOQ of and 50 and100 ng/mL[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the preferred anti-hydatid drug, ABZ has a very fast metabolic rate in plasma ( 35 ). After oral administration, ABZ is rapidly transformed into ABZ sulphoxide (ABZSO) and ABZSO 2 (of which ABZSO is the main active substance) and finally into albendazole-2-aminosulfone (ABZSO 2 -NH 2 ) under the action of various enzyme systems in the liver ( 36 ).…”
Section: Methodsmentioning
confidence: 99%